Electrowinning of Iron from Spent Leaching Solutions Using Novel Anion Exchange Membranes - Badenhorst, Wouter Dirk (Membranes (Basel), 2019)
In the Pyror process, electrowinning (EW) is used to recover acid and iron from spent leaching solutions (SLS), where a porous Terylene membrane acts as a separator between the cathode and anode. In this study, a novel anion exchange membrane (AEM)-based EW process is benchmarked against a process without and with a porous Terylene membrane by comparing the current efficiency, specific energy consumption (SEC), and sulfuric acid generation using an in-house constructed EW flow cell. Using an FAP-PK-130 commercial AEM, it was shown that the AEM-based process was more efficient than the traditional processes. Subsequently, 11 novel polybenzimidazole (PBI)-based blend AEMs were compared with the commercial AEM. The best performing novel AEM (BM-5), yielded a current efficiency of 95% at an SEC of 3.53 kWh/kg Fe, which is a 10% increase in current efficiency and a 0.72 kWh/kg Fe decrease in SEC when compared to the existing Pyror process. Furthermore, the use of the novel BM-5 AEM resulted in a 0.22 kWh/kg Fe lower SEC than that obtained with the commercial AEM, also showing mechanical stability in the EW flow cell. Finally, it was shown that below 5 g/L Fe, side reactions at the cathode resulted in a decrease in process efficiency, while 40 g/L yielded the highest efficiency and lowest SECs.